2021
DOI: 10.2147/idr.s332148
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and Treatment Success in Drug-Resistant Tuberculosis in Uganda

Abstract: Background Undernutrition is associated with unfavourable treatment outcomes among people with drug-resistant tuberculosis (DRTB). Factors influencing the treatment outcomes among undernourished people with DRTB are not well characterised. The aim of this study was to determine factors associated with treatment success among undernourished people with DRTB in Uganda. Methods We analysed data from a retrospective cohort of people with DRTB from 16 treatment sites in Ugan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
(57 reference statements)
2
5
0
Order By: Relevance
“…MUAC measurement, an indicator of patient nutrition status was also found to be predictive of non-adherence. This concurred with two different studies (72,73) both conducted in Uganda, among tuberculosis patients, that found that undernutrition leads to unfavorable treatment outcomes. This finding also resonated with the fact that tuberculosis drugs are administered according to patient weight at diagnosis.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 87%
“…MUAC measurement, an indicator of patient nutrition status was also found to be predictive of non-adherence. This concurred with two different studies (72,73) both conducted in Uganda, among tuberculosis patients, that found that undernutrition leads to unfavorable treatment outcomes. This finding also resonated with the fact that tuberculosis drugs are administered according to patient weight at diagnosis.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 87%
“…It was interesting to observe a disconnect in the prevalence of obesity as measured by the BMI (4.0%) and waist-hip ratio/waist circumference (39.3%) in our study. In fact, undernutrition, as measured by the BMI is very prevalent among people with DRTB in Uganda [ 49 ]. However, similar to our findings, central obesity was prevalent in 33% of people with TB and it correlated with DM better than the BMI in a study from the Philippines [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GNRI seems to have a better ability to predict the risk of all-cause death than BMI, but this difference has not reached statistical significance. Many studies 3,[17][18][19] showed a close relationship between malnutrition and the occurrence of pulmonary TB, but it has not been clarified whether malnutrition increases the short-term mortality risk of pulmonary TB, the results of univariate analysis generally tended that malnutrition was a factor affecting the mortality risk of TB patients. However, the results of the multivariate analysis were different.…”
Section: Discussionmentioning
confidence: 99%